Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.